Trastuzumab-induced cardiac dysfunction: A ‘dual-hit’ - Zeglinski, Matthew (Pulsus Group Inc, 2011)
Trastuzumab (Trz) is a monoclonal antibody against the human epidermal growth factor receptor 2 that is found to be overexpressed in 25% to 30% of breast cancer patients. In spite of the therapeutic benefits of Trz, cardiotoxic side effects are still an issue. This effect is potentiated particularly when Trz is administered following doxorubicin (DOX) treatment. Among the various mechanisms that may account for DOX and Trz-induced cardiotoxicity, the role of oxidative stress has gained significant support. The present review discusses the evidence supporting the hypothesis that oxidative stress comes from multiple sources through an increase in the production of reactive oxygen species and/or a decrease in antioxidant defense systems. The adjuvant use of Trz can potentiate cardiomyocyte damage through a ‘dual-hit’ mechanism, which includes inhibition of the neuregulin-1 survival signalling pathway and angiotensin II-induced activation of NADPH oxidase, with the ability to further increase reactive oxygen species production. Preventive therapies for DOX- and Trz-induced cardiac dysfunction have eluded investigators, but may include the prophylactic use of angiotensin-converting enzyme inhibitors, beta-blockers and use of antioxidants. Thus, a better understanding of the mechanisms leading to this characteristic drug-induced cardiomyopathy, as well as potential cardioprotective strategies is required.